Impacto da pureza dos filtros de alumínio no valor de Camada Semi-Redutora em radiologia convencional e mamografia (Brazilian Journal of Radiation Sciences, 2016)
Half Value Layer (HVL) test is an important technical information in conventional radiology once it is the only test which allows us to quantify beam quality in a complete way. This work promotes a preliminary analysis of the impact of aluminum alloy composition in the determination of HVL value taking into account a realistic geometry. Deterministic calculations and Monte Carlo Method were applied in order to make the proposed analysis. Six aluminum alloys (99% pure) commercialized and pure aluminum were used as comparative basis for both methods. Experimental data were collected in conventional radiology, using tungsten target and aluminum filter for two peak tensions (66 kVp, 81 kVp), and in mammography, using three target filter combinations( molybdenum-molybdenum, molybdenum-rhodium, tungsten-rhodium) for three peak tensions (25 kVp, 30 kVp and 35 kVp). Spectra used in the deterministic calculations were taken from Report No 78 of Institute of Physics and Engineering in Medicine, 1997. Results show that Mammography is more sensitive than conventional X-ray equipment to impurities in aluminum alloys (up to 34.65% variation for W-Rh combination with 30 kVp).
Keywords: Radiology; mammography; dosimetry.